Evaluation of Immunity enhancing activity of Cladophora glomerata crude extracts and phytol in male albino mice (World Journal of Experimental Biosciences, 2016)
Cladophora glomerata is the most widely distributed macroalga throughout the world’s freshwater ecosystems. The immunological effects of C. glomerata in the present study were evaluated. The algal samples were collected from the fresh water in the canal around University of Baghdad. The GC- Mass analysis of crude algal extracts (aqueous and alcoholic) was carried out and the active chemical compounds in algal extracts were described. Phytol represented the highest one between the other compounds in alcoholic extract. Our study provides for the first time immunological effects of C. glomerata and phytol on interleukins (IL-2 and IL-4) and interferon-gamma levels. The production of IL-2 was increased as dose - dependent manner in all treated groups of mice. The production of IL-4 was also increased as dose-dependent manner in both alcoholic extract and phytol. The current study revealed that the aqueous extract increased IFN-γ as dose dependent manner, while the higher dose of alcoholic extract and phytol decreased IFN-γ. In addition, the lower dose of alcoholic extract increased IFN-γ. The data of this study suggested that the both crude extracts of C. glomerata and phytol can be used as immune-stimulator.